Tracheostomy in motor neuron disease - Turner, M; Faull, C; McDermott, C; Nickol, A; Palmer, J; Talbot, K (BMJ Publishing Group, 2019)
Tracheostomy-associated ventilation for the respiratory insufficiency caused by amyotrophic lateral sclerosis (motor neurone disease (MND)) is a complex issue with practical, ethical and economic dimensions. This article considers the current prevalence of tracheostomy in MND, the evidence for its benefit both for survival and quality of life, and the practicalities of its implementation. The decision to request invasive ventilatory support is among the most challenging for those living with MND. Neurologists should be prepared to discuss this option openly and objectively: we suggest a framework for discussion, including withdrawal of therapy.